Relationship between bully victimization and emotional difficulty in adolescence: hope and school connectedness as mediator - Yusop, Yusni Mohamad; Soon, Tiew Wah; Wan Othman, Wan Norhayati; Zainudin, Zaida Nor; Mohd Puad, Dharatun Nissa (Human Resource Management Academic Research Society, 2023)
It has been known that bullying victimization could lead to emotional difficulties. Current study wished to examine what could be the underlying factors that leads to this relationship and by identify the potential factors, counsellor will be able to have different approach to help victim of bullying. This study focused on the relationship between bullying victimization and emotional difficulties and mediation effect of hope and school connectedness. There are total of 413 respondent participated in this study. Descriptive analysis was used to determine the demographic data. Pearson correlation shows that all four variables are significantly associated with each other. In the mediation analysis, finding shows that hope has partial mediation effect while school connectedness does not have mediation effect. The results were discussed and implication of study has been included into the study. Finding of current study has contributed to the literature gap and the mediation effect shown by hope will serve as new method to reduce the negative effect of bully.